Tjänstemarknadsföring inom fastighetsförmedling - Samuelson, Carl-Adam (2008)
Services, no matter if they are established on the market or not, are often problematic since they are difficult to define for the customer. An example of such services is an real estate agent offers his or her service when it comes to all types of real estate. The purpose of the intermediation is to sell a costumers real estate to a buyer and act arbitrator between the two parties, this means that good communication is very important. To pin down what the service is all about and to know how to communicate is essential. When it comes to land and forest holding a special need of knowledge and experience is needed to be able to act professionally. The purpose of this thesis is to highlight and analyze the role agents that take on the role as that intermediate land and forest holding. The analysis is divided into three parts, the estate agents background, and his or her view of his and her service and the costumers point of view of the service that the real estate agent offers.